1995
DOI: 10.1002/jsfa.2740680116
|View full text |Cite
|
Sign up to set email alerts
|

Natural decoloration, composition and increase in dietary fibre content of an edible marine algae, Ulva rigida (Chlorophyta), grown under different nitrogen conditions

Abstract: The colour, dietary fibre content and characteristics of the edible marine green algae, Uloa rigida, were investigated in relation with the nitrogen content of the algal culture medium. Colour brightness decreased and total nitrogen of the algae increased in nitrogen-enriched conditions. When nitrogenenriched seaweeds were grown again in normal seawater for 10 days, colour brightness increased and total nitrogen concentration fell. Total dietary fibre content of the wild and nitrogen enriched algae were close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
4
19
2
1
Order By: Relevance
“…This is in agreement with Lahaye et al (1995) who reported that the nitrogen content in the culture medium affects the biosynthesis of the algal cell wall polysaccharides as well as of proteins and pigments. Gómez-Pinchetti et al (1998) also reported, for U. rigida, that when nitrogen limits growth, carbohydrate synthesis predominates and in nitrogen enriched conditions, a decrease in fibre content is observed.…”
Section: Crude Protein Ash and Dietary Fibresupporting
confidence: 93%
See 4 more Smart Citations
“…This is in agreement with Lahaye et al (1995) who reported that the nitrogen content in the culture medium affects the biosynthesis of the algal cell wall polysaccharides as well as of proteins and pigments. Gómez-Pinchetti et al (1998) also reported, for U. rigida, that when nitrogen limits growth, carbohydrate synthesis predominates and in nitrogen enriched conditions, a decrease in fibre content is observed.…”
Section: Crude Protein Ash and Dietary Fibresupporting
confidence: 93%
“…SDF in U. clathrata cultivated samples (16-22% dw) represented the main fraction of dietary fibre (>50% of TDF) and, although SDF% dw was higher for LSS Ulva sample, the soluble to insoluble dietary fibre ratio (S/I) was significantly lower (1.2) for LSS sample vs MSS samples (1.7avg), because the IDF increases at higher rate than the SDF in LSS. In Lahaye et al (1995) study, growing conditions also affected the S/I ratios. The higher proportion of soluble polysaccharides, in nitrogen enriched U. rigida (S/I = 1.23) than in wild algae (S/I = 0.93), was related to its high growth rate.…”
Section: Crude Protein Ash and Dietary Fibrementioning
confidence: 78%
See 3 more Smart Citations